(3EcSjd (B2003 (3ahQOGejR (B= Excel 2003 for dummies /s - (3LQjL gGQajs; (3NGdO GdYGeQjs ((3GdbGgQI (B:s (3OGQ GdaGQhb ddfTQ hGdJhRjY,s, 2004)
(3jSGYO HQfGeL GdGcSjd Ydi JfXje GdeYdheGJ HhGSWI GdLOGhd GdCdcJQhfjI h GdJNWjWGJ h GdQShe GdHjGfjI (B.s
Keywords: (3eGjcQhShaJ EcSds; (3eGjcQhShaJ ChajS(B.s